The Effectivity of Muntingia calabura L. Leaf Extract Cream on Skin Incision Wound Healing Day 7 on White Rat (Rattus Norvegicus) with Diabetes Mellitus - Salim, M Nur; Masyitha, Dian; Hennivanda, Hennivanda; Aisyah, Siti; Daud, Razali; Sabri, Mustafa; Fitria, Dinda (Jurnal Medika Veterinaria, 2023)
Wounds are damage to tissue integrity and function that occurs in the body. High blood glucose levels in diabetes mellitus can inhibit wound healing. This study aimed to determine the effectiveness of kersen leaf extract cream (Muntingia calabura L.) on the healing process of incision wounds on the skin of white rats (Rattus norvegicus) with diabetes mellitus on day 7. The experimental animal used were 12 male white rats weighing 150-200 g, aged 2-3 months old which were induced by streptozotocin 45 mg/kg BW intraperitonially. This research method used a completely randomized design (CRD) consisting of K1 as a negative control given a cream base and distilled water, K2 as a positive control given 0,1% silver sulfadiazine cream and metformin 4.5 mg/kg BW, K3 and K4 given 5% and 15% kersen leaf extract cream and 450 mg/kg BW kersen leaf extract orally. Incision wounds were made in the paravetebral area along 2 cm with a depth of 2 mm. Wound care was performed twice a day for 7 days. ANOVA test result showed that the administration of cream and kersen leaf extract significantly affected the number of fibroblast cells, collagen, and angiogenesis. The results showed that K1 was significantly different (P0,05) from K2, K3 and K4. K3 and K4 groups had higher average numbers of fibroblast cells, collagen, and angiogenesis. The application of kersen leaf extract cream was able to increase the number of fibroblast cells, collagen, and angiogenesis so that it could accelerate the healing of incision wound on day 7 in white rats with diabetes mellitus.